2013
DOI: 10.1038/ja.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

New phenethylamine derivatives from Arenibacter nanhaiticus sp. nov. NH36AT and their antimicrobial activity

Abstract: Five new phenethylamine (PEA) derivatives (1-5) were isolated from the strain of Arenibacter nanhaiticus sp. nov. NH36A(T) derived from the marine sediment of the South China Sea by bioassay-guided fractionation. Their structures were elucidated by spectroscopic methods including UV, IR, HR-MS and NMR. Interestingly, compounds 1-4 existed as enantiomers, which were resolved by chiral liquid chromatography. The resolved configuration of each enantiomer was assigned by the Marfey's method. Of these compounds, 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Our finding, together with previous reports, indicates that the production of PEA-containing alkaloids is likely a widespread characteristic within the marine flavobacteria. For instance, in a previous report five PEA derivatives were isolated from the flavobacterial strain Arenibacter . In addition, PEA was proposed as a taxonomic biomarker within the free-living Bacteroidetes phylum .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding, together with previous reports, indicates that the production of PEA-containing alkaloids is likely a widespread characteristic within the marine flavobacteria. For instance, in a previous report five PEA derivatives were isolated from the flavobacterial strain Arenibacter . In addition, PEA was proposed as a taxonomic biomarker within the free-living Bacteroidetes phylum .…”
Section: Results and Discussionmentioning
confidence: 99%
“…For instance, in a previous report five PEA derivatives were isolated from the flavobacterial strain Arenibacter. 47 In addition, PEA was proposed as a taxonomic biomarker within the free-living Bacteroidetes phylum. 48 These studies together with our findings revealed that the genus Tenacibaculum and other flavobacterial strains are able to produce this type of arylamine.…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
“…Phenethylamine derivatives isolated from the strain of Arenibacter nanhaiticus sp. nov. NH36AT consist of antimicrobial activity against Staphylococcus aureus and Bacillus subtilis, Escherichia coli [ 163 ]. Lactobacillus iners also produce a moderate level of lactic acid and prevent BV [ 164 ].…”
Section: Microbiota Metabolites Therapeutic Insight In Ptbmentioning
confidence: 99%
“…The antimicrobial activity against E. coli, S. aureus, C. albicans, and A. niger were evaluated by an agar dilution method [19]. The tested strains were cultivated on MH agar plates for bacteria at 35C.…”
Section: Methodsmentioning
confidence: 99%